Enzalutamide in European and North American men participating in the AFFIRM trial. (23rd October 2014) - Merseburger, Axel S.; Scher, Howard I.; Bellmunt, Joaquim; Miller, Kurt; Mulders, Peter F.A.; Stenzl, Arnulf; Sternberg, Cora N.; Fizazi, Karim; Hirmand, Mohammad; Franks, Billy; Haas, Gabriel P.; de Bono, Johann; et al.
<x xml:space="preserve">Abstract</x> Objective To explore any differences in efficacy and safety outcomes between European (EU) (n = 684) and North American (NA) (n = 395) patients in the AFFIRM trial (NCT00974311). Patients and Methods Phase III, double‐blind, placebo‐controlled, multinational AFFIRM trial in men with metastatic castration‐resistant prostate cancer (mCRPC) after docetaxel. Participants were randomly assigned in a 2:1 ratio to receive oral enzalutamide 160 mg/day or placebo. The primary end point was overall survival (OS) in a post hoc analysis. Results Enzalutamide significantly improved OS compared with placebo in both EU and NA patients. The median OS in EU patients was longer than NA patients in both treatment groups. However, the relative treatment effect, expressed as hazard ratio and 95% confidence interval, was similar in both regions: 0.64 (0.50, 0.82) for EU and 0.63 (0.47, 0.83) for NA. Significant improvements in other end points further confirmed the benefit of enzalutamide over placebo in patients from both regions. The tolerability profile of enzalutamide was comparable between EU and NA patients, with fatigue and nausea the most common adverse events. Four EU patients (4/461 enzalutamide‐treated, 0.87%) and one NA patient (1/263 enzalutamide‐treated, 0.38%) had seizures. The difference in median OS was related in part to the timing of development of mCRPC and baseline demographics on study entry. Conclusion This post hoc exploratory analysis of the AFFIRM trial showed a consistent OS benefit for enzalutamide in men with mCRPC who had previously progressed on docetaxel in both NA‐ and EU‐treated patients, although the median OS was higher in EU relative to NA patients. Efficacy benefits were consistent across end points, with a comparable safety profile in both regions.